THE HYGIENIC CONTROL OF FREQUENTLY ILL CHILDREN IN PRESCHOOLS - Imamova Akida Obidjon qizi; Khobiljonova Shakhnoza Rustam qizi (Innovate Conferences, 2025)
Frequent illnesses among preschool children present significant challenges in early childhood education settings. Implementing effective hygienic control measures is crucial to mitigate the spread of infections and promote a healthy environment. This article examines the impact of hygiene practices on the health of frequently ill children in preschool kindergartens. Through a comprehensive review of existing literature, we identify key hygienic interventions that reduce illness incidence, including proper hand hygiene, effective cleaning protocols, and educational initiatives. The findings underscore the importance of stringent hygiene practices in safeguarding child health within preschool environments.
Keywords: Preschool hygiene, infection control, child health, handwashing, sanitation practices, early childhood education